ATF3 Protects Pulmonary Resident Cells from Acute and Ventilator-Induced Lung Injury by Preventing Nrf2 Degradation - Shan, Yuexin (Antioxid Redox Signal, 2015)
Aims: Ventilator-induced lung injury (VILI) contributes to mortality in patients with acute respiratory distress syndrome, the most severe form of acute lung injury (ALI). Absence of activating transcription factor 3 (ATF3) confers susceptibility to ALI/VILI. To identify cell-specific ATF3-dependent mechanisms of susceptibility to ALI/VILI, we generated ATF3 chimera by adoptive bone marrow (BM) transfer and randomized to inhaled saline or lipopolysacharide (LPS) in the presence of mechanical ventilation (MV). Adenovirus vectors to silence or overexpress ATF3 were used in primary human bronchial epithelial cells and murine BM-derived macrophages from wild-type or ATF3-deficient mice. Results: Absence of ATF3 in myeloid-derived cells caused increased pulmonary cellular infiltration. In contrast, absence of ATF3 in parenchymal cells resulted in loss of alveolar-capillary membrane integrity and increased exudative edema. ATF3-deficient macrophages were unable to limit the expression of pro-inflammatory mediators. Knockdown of ATF3 in resident cells resulted in decreased junctional protein expression and increased paracellular leak. ATF3 overexpression abrogated LPS induced membrane permeability. Despite release of ATF3-dependent Nrf2 transcriptional inhibition, mice that lacked ATF3 expression in resident cells had increased Nrf2 protein degradation. Innovation: In our model, in the absence of ATF3 in parenchymal cells increased Nrf2 degradation is the result of increased Keap-1 expression and loss of DJ-1 (Parkinson disease [autosomal recessive, early onset] 7), previously not known to play a role in lung injury. Conclusion: Results suggest that ATF3 confers protection to lung injury by preventing inflammatory cell recruitment and barrier disruption in a cell-specific manner, opening novel opportunities for cell specific therapy for ALI/VILI. Antioxid. Redox Signal. 22, 651–668.